YAP1 and TAZ control pancreatic cancer initiation in Mice by Direct Up-regulation of JAK-STAT3 signaling - Gruber,R; Panayiotou,R; Nye,E; Spencer-Dene,B; Stamp,G; Behrens,A (Gastroenterology, 2016)
Background & AimsPancreatitis is the most important risk factor for pancreatic ductal adenocarcinoma (PDAC). Pancreatitis predisposes to PDAC because it induces a process of acinar cell reprogramming known as acinar-to-ductal metaplasia (ADM)—a precursor of pancreatic intraepithelial neoplasia lesions that can progress to PDAC. Mutations in KRAS are found at the earliest stages of pancreatic tumorigenesis, and it appears to be a gatekeeper to cancer progression. We investigated how mutations in KRAS cooperate with pancreatitis to promote pancreatic cancer progression in mice.MethodsWe generated mice carrying conditional alleles of Yap1 and Taz and disrupted Yap1 and Taz using a Cre-lox recombination strategy in adult mouse pancreatic acinar cells (Yap1fl/fl;Tazfl/fl;Ela1-CreERT2). We crossed these mice with LSL-KrasG12D mice, which express a constitutively active form of KRAS after Cre recombination. Pancreatic tumor initiation and progression were analyzed after chemically induced pancreatitis. We analyzed pancreatic tissues from patients with pancreatitis or PDAC by immunohistochemistry.ResultsOncogenic activation of KRAS in normal, untransformed acinar cells in the pancreatic tissues of mice resulted in increased levels of pancreatitis-induced ADM. Expression of the constitutive active form of KRAS in this system led to activation of the transcriptional regulators YAP1 and TAZ; their function was required for pancreatitis-induced ADM in mice. The JAK–STAT3 pathway was a downstream effector of KRAS signaling via YAP1 and TAZ. YAP1 and TAZ directly mediated transcriptional activation of several genes in the JAK–STAT3 signaling pathway; this could be a mechanism by which acinar cells that express activated KRAS become susceptible to inflammation.ConclusionsWe identified a mechanism by which oncogenic KRAS facilitates ADM and thereby generates the cells that initiate neoplastic progression. This process involves activation of YAP1 and TAZ in aci